Efeito do regulador de crescimento trinexapac-ethyl em cultivares de arroz irrigado - Estevo, Ana Paula (2013)
This study aims to evaluate the effects of plant growth regulator trinexapac-ethyl on rice cultivars, checking agronomically feasible dose and the effect of these doses on the morphology of plants on yield components and on reducing lodging plant. In this sense, two trials were held, one in the field to evaluate the effects of doses of trinexapac-ethyl on yield components over the biological cycle, about flowering. The second study was performed in greenhouse. The objective is evaluate the effects of increasing doses of trinexapac-ethyl on the morphology of plants of two cultivars of rice: a japonica cultivar (Bojurú) and one Indica cultivar (IRGA 422 CL). Experimental results show that the plant growth regulator trinexapac-ethyl applied in increasing doses, causes changes in the morphology of plants, shortening between-us, reducing plant height, leaf area and interfering in shoot dry mass, reducing bedding plants and interfering negatively in yield components, especially in the percentage of whole grains and broken grains.